Hakikat Alam Semesta Menurut Pandangan Islam dan Kaitannya dengan Pendidikan Islam - Wildan Murtadho; Zukhrufi Ihtimami Tanjung; Nurul Fiza Azizi Hasibuan (Swakarya: Jurnal Penelitian Sosial dan Pengabdian Masyarakat, 2025)
This paper discusses the nature of the universe from an Islamic perspective and its implications for Islamic education. The universe is a creation of God that has order and educational values and is an object of contemplation and study in Islam. With a literature study approach, this study explores the concept of cosmology in the Qur'an, the views of Muslim philosophers and Sufis such as al-Farabi, Ibn Sina, and Ibn 'Arabi, and modern scientific theories such as the Big Bang. The results of the study show that the universe is not only a physical reality, but also has deep spiritual and philosophical values, which lead to the recognition of the greatness and power of God. In the context of Islamic education, understanding the universe encourages the integration of science with the values of faith, makes nature a medium of learning, and strengthens the function of humans as caliphs on earth. Practical implications include the formation of student characters who love knowledge, have noble morals, and are environmentally conscious.